EFEKTIFITAS PIJAT BAYI DAN FOTOTERAPI TERHADAP KADAR BILIRUBINEMIA PADA BAYI BARU LAHIR DI RUMAH SAKIT AMINAH TANGERANG - Indriari, Rizka; Simanullang, Rostime Hermayerni (STIKes Murni Teguh, 2025)
Hyperbilirubinemia is a condition that often occurs in newborns and can cause various complications if not treated properly. This study aims to evaluate the effectiveness of infant’s massage and phototherapy on bilirubinemia levels in newborns at Aminah Hospital Tangerang. The study method is quantitative with cross sectional design. The sample in this study amounted to 75 respondents with purposive sampling technique. Data analysis used the Spearman Rho test. The results of this study using the Sperman test showed the effectiveness of infant massage and phototherapy on bilirubinemia levels in newborns at Aminah Hospital as indicated by a p-value <0.05. It is concluded that there was effectiveness of infant’s massage and phototherapy on bilirubinemia levels in newborns. It is recommended for further research to add variable of Fluid Intake, and Length of Treatment.